Enhanced dielectric and conductivity properties of carbon-coated SiC nanocomposites in the terahertz frequency range. (9th April 2021) - Huang, Feirong; Fan, Shuting; Li, Xiyang; Qu, Xinghao; Tian, Yuqi; Zhang, Xuefeng; Zhang, Zhidong; Dong, Xinglong; Cao, Tun
Abstract: C-coated SiC nanocomposites (SiC@C NCs) were one-step synthesized under a mixture atmosphere of Ar and CH4 using a DC arc-discharge plasma method. The microstructure of the composites could be controlled by varying the volume ratio of Ar and CH4 . A strong response to the terahertz (THz) field was observed due to the existence of a graphite shell. The dielectric properties of SiC@C NCs can be enhanced by altering the thickness of the graphite shell. The thicker graphite shell results in a stronger absorption of THz waves and an enhanced real part of conductivity. Fitting the measured conductivity data using the Drude–Smith model reveals that the carrier transport in the SiC@C NCs and its counterpart, the SiC nanoparticles, is dominated by backscattering. The SiC@C NCs with enhanced conductivity are believed to be fundamental materials for various functionalized optoelectronic devices.